A Family-Focused Intervention for Parental Mental Illness: A Practitioner Perspective - Furlong, Mairead; Mulligan, Christine; McGarr, Sharon; O'Connor, Siobhan; McGilloway, Sinead (Frontiers in Psychiatry, 2021)
Background Parental mental illness (PMI) is common and can lead to children developing mental disorders. Family Talk (FT) is a well known and widely implemented intervention designed to reduce the risk of transgenerational psychopathology. However, given the research to practice ‘gap’, very little qualitative research, to date, has investigated practitioner experiences in implementing FT. This study aimed to explore the practitioner-perceived barriers and facilitators to the implementation and sustainability of FT within mainstream mental health settings. Methods This study was nested within a randomised controlled trial (RCT) of Family Talk (N=86 families [139 parents, 221 children]) within 15 adult (AMHS), child (CAMHS), primary care mental health, and child protection sites in Ireland. Semi-structured interviews and focus groups were undertaken with a purposive sample of clinicians (n=31) and managers (n=10), based on their experiences of implementing FT. Interview data were transcribed verbatim, analysed using constructivist grounded theory, and informed by Fixsen’s implementation science framework. Results Service providers highlighted a number of benefits for approximately two thirds of families across different diagnoses and mental health settings (AMHS/CAMHS/primary care). Sites varied in their capacity to embed FT, with key enablers identified as acquiring managerial and organisational support, building clinician skill, and establishing interagency collaboration. Implementation challenges included: recruitment difficulties, stresses in working with multiply-disadvantaged families, disruption in delivery due to the COVID-19 global pandemic, and sustainability concerns (e.g. perceived fit of FT with organisational remit/capacity, systemic and cultural barriers to change). Conclusion This study is only the second qualitative study ever conducted to explore practitioner experiences in implementing FT, and the first conducted within the context of an RCT and national research programme to introduce family-focused practice (FFP) for families living with PMI. The findings illuminate the successes and complexities of implementing FFP in a country without a ‘think family’ infrastructure, whilst highlighting a number of important generalisable lessons for the implementation of FT, and other similar interventions, elsewhere.